'Extreme personal stress' and 'a lot of pain': Exploring the physical, mental and social contexts of extramedical pharmaceutical opioid use in Australian paramedic case descriptions. (7th July 2020) - Wilson, James; Lam, Tina; Scott, Debbie; Crossin, Rose; Matthews, Sharon; Smith, Karen; Lubman, Dan I.; Nielsen, Suzanne
Abstract: Introduction and Aims: Despite growing concerns over the extramedical use of pharmaceutical opioids, few studies have focused on the contexts that shape this use or how it might lead to harm. There is also limited research examining how contexts might vary across different opioids, such as those with well‐established abuse liabilities (e.g. oxycodone) and newer 'atypical' opioids (e.g. tapentadol). We aimed to address these gaps. Design and Methods: We analysed Australian paramedic case descriptions for tapentadol cases ( n = 82) and a representative sample of oxycodone cases ( n = 82) from a 6‐year period (2013–2018). We used framework analysis to identify 'contexts' shaping extramedical use from cases where use of tapentadol or oxycodone was assessed to have significantly contributed to the attendances. Results: Demographically, case descriptions from both drug types were broadly similar (approximately 55% female, 44% were 35–54 years old), as were the contextual factors. The most prevalent contexts common to both oxycodone and tapentadol cases were psychological distress, physical pain and social stressors. Suicidal intent was present across multiple contexts. Discussion and Conclusions: This study is one of the first to explore the contexts of extramedical pharmaceutical opioid use leading to acute harm. Our analysis found patients in complex, emergency situations, seeking rapid relief from physical pain, psychological distress, social issues and/or suicidal thoughts. These data highlight the complex needs of those experiencing harm from extramedical pharmaceutical opioid use, regardless of opioid type, and the importance of contextual factors shaping both use and subsequent harm.